Prisoners’ Perceptions of Father-Child Relationships and Social Support - Swanson, Cheryl (American journal of criminal justice, 2012)
Incarcerated fathers ( N = 185) in a maximum security prison were interviewed about their relationship with their children and their perceptions of social support. The OLS regression on social support included the inmates’ perception of the father-child relationship and other factors (demographic, sentence, child-related, and program participation). Results indicate the fathers’ perception of the relationship with their children made a positive contribution to their appraisal of social support from all sources. “Other” program participation and being African American were related to the fathers’ perception of social support from others. Recommendations include using social support strategies in pre-release and post-release programs.